A case of insulinoma effectively treated with low‐dose diazoxide - Atsushi Yasuda; Toshiro Seki; Natsumi Kitajima; Tanefumi Baba; Noriko Sasaki; Yoshie Kametani; Masami Seki; Kazuko Tanaka; Masayuki Oki (Clinical Case Reports, 2020)
Abstract Diazoxide is a benzothiadiazine that can be effective in managing hypoglycemia in frail patients with surgical risk. We report here a case of insulinoma effectively treated with diazoxide, as our report will be helpful for similar cases.